Technology, Factor Supplies, and International Specialization: Estimating the Neoclassical Model - Harrigan, James (American Economic Review, 1997)
The neoclassical model of trade predicts that international specialization will be jointly determined by cross-country differences in relative factor endowments and technology levels. This paper specifies an empirical model of specialization consistent with the neoclassical explanation. In the model, a sector's share of GDP depends on relative factor supplies and relative technology differences, and the estimated parameters of the model have a clear connection to theoretical parameters. The model is estimated with panel data on manufacturing sectors in industrialized countries. Relative technology levels and factor supplies are both found to be important determinants of specialization.